Quality of Banking Services as a Source of Competitive Advantage - Klimontowicz, Monika (Jakość usług bankowych jako źródło przewagi konkurencyjnej, 2010)
Owing to increased competition of the financial service industry, internationalization and globalization, implementing new products, changes in consumer needs and technological progress, banks find themselves faced with the necessity of specifying the determinants of competitive advantage and banks's strategy redefinition. Undoubtedly the service quality is the item that creates the loyalty of customers and competitive advantage in a long-term perspective. Focusing on the service quality results in an improvement of bank's image and an increase of incomes. The purpose of this paper is to present the role of service quality among other competitive advantage factors and its place in banks' strategy focused on gaining consumer's satisfaction and advantage.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 125, s. 78-94
Keywords: service quality; intangible assets; banks' competitive advantage